Discovering meanings from transcribed interviews: Discussions on the use of contents analysis (as the primary data collection technique) - Othman, Norazam (2007)
The aim of the research is to investigate the influence of contractual procedures on construction professionals' working practices. Theoretically the use of contractual procedures, as prescribed in standard forms of contract, is to establish a high degree of rationality on an inherently unpredictable and irrational situation that is the construction project. Thus research questions were directed to elucidate how and why contractual procedures are used whenever construction professionals are doing their task. Data to be collected is the thoughts and actions of the professionals who used procedures in dealing with a specific task. However, there is a possibility that speakers may mean something different from what they say to show that the account of a particular activity is rational or justified. Thus content analysis of the semi-structured interviews were conducted to discover the meanings that a respondent actually alluded to since it is located and indexed within the expressions used to describe, explain or justify a specific task, event or occasion. Finally, framing the research within a case study methodology ensures the preservation of the unitary character of the social object being studied. Findings suggest that although construction professionals are influenced by procedures and/or rules codified in standard forms of contract, other traces of influence are also present. The mode of inquiry adopted means that the research is not concerned with noting the frequency or occurences of usage of contractual procedures and/or rules but rather to illustrate and identify these influences. The findings may be used for future contract drafting policies as the profileration of new standard forms or conditions of contract in Malaysia’s construction industry suggest that present documents are less than ideal or even treating construction contracts as distinct since classical model of contract does not seem to address the complexities nor subtleties of the construction process.